Functional Outcomes and Patient Satisfaction After Fasciotomy for Chronic Exertional Compartment Syndrome. (February 2013) - Packer, Jonathan D.; Day, Michael S.; Nguyen, Joseph T.; Hobart, Sarah J.; Hannafin, Jo A.; Metzl, Jordan D.
Background: Patients with chronic exertional compartment syndrome who have failed nonoperative treatment are evaluated with pre-exertion and postexertion compartment pressure testing and may be treated with fasciotomy. Failure rates of up to 20% have been reported and may be related to factors such as age, sex, postexertion compartment pressures, compartment(s) released, and duration of symptoms. Hypothesis: Higher preoperative postexertion compartment pressures are correlated with higher success and patient satisfaction rates after fasciotomy. Study Design: Cohort study; Level of evidence, 3. Methods: From 1999 to 2008, patients with clinical symptoms of chronic exertional compartment syndrome with failed nonoperative management underwent standardized pre-exertion and postexertion compartment pressure measurements. Patients were then offered continued nonoperative treatment or referral to an orthopaedic surgeon for compartment release. Patients with a minimum 2-year follow-up were given a telephone questionnaire describing their pretreatment and posttreatment conditions including quality and duration of symptoms, analog pain scale, symptomatic and functional responses to treatment, and satisfaction with treatment. Medical records and operative reports were reviewed. Results: The mean follow-up period for the nonoperative treatment group (n = 27) was 5.6 years (range, 2.1-10.6) and for the operative group (n = 73) was 5.2 years (range, 2.0-11.3). The operative group had a higher success rate (81%) compared with the nonoperative group (41%) ( P < .001), and the operative group had a higher patient satisfaction rate (81%) compared with the nonoperative group (56%) ( P = .011). There was no significant correlation between compartment pressures and patient outcomes. Patients with combined anterior and lateral compartment releases had an increased failure rate compared with isolated anterior release (31% vs 0%, respectively; P = .035). Surgical patients who were post-college had a lower satisfaction rate (66%) compared with high school (89%) and college patients (94%) ( P = .017). Conclusion: High school and college patients (age <23 years) and isolated anterior compartment release (compared with anterior/lateral release) were factors associated with improved subjective function and satisfaction after fasciotomy. We recommend the avoidance of lateral release unless symptoms or postexertion compartment pressures are clearly indicative of lateral compartment involvement.